Intramuscular Lipoma within a Free Myocutaneous Flap: Systematic Review and Management - Kenny, Elizabeth M.; Egro, Francesco M.; Acartürk, Tahsin Oğuz (Journal of Hand and Microsurgery, 2018)
Lipomas are a common finding often of little clinical significance, but they can pose a challenge to the microsurgeon if discovered during flap harvesting, especially if found within the muscle along the pedicle or perforators. Here the authors report a case in which a well-circumscribed intramuscular lipoma was discovered within the muscle of a free myocutaneous right anterolateral thigh (ALT) vastus lateralis free flap. To the authors’ knowledge, the management of lipoma during flap harvesting has not been previously discussed in the literature. A systematic review was performed, and an approach for the management of myocutaneous flaps containing a lipoma was described. Underappreciated considerations including lipoma location, growth pattern, and proximity to pedicle and perforators must be taken into account when evaluating a lipoma during flap harvest.
Keywords: lipoma; free flaps; review; systematic; approach; microsurgery